Gambaran pengetahuan mahasiswa mengenai perbedaan efektivitas clear aligner dengan ortodonti cekat : Kajian pada Mahasiswa FKG USAKTI angkatan 2019 (Laporan Penelitian) - Adinda Disa Murbarani; Himawan Halim (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: The high popularity of orthodontics appliances, such as fixed orthodontics (braces) and clear aligners coincides with the demand of increasing ones’ appearance in society whilst maintaining aesthetic. Objective: To obtain a picture of the understanding that Trisakti University second-year dental students have, regarding the differences in the effectiveness of clear aligner and fixed orthodontics treatment based on prior knowledge. Method: Descriptive observational research together with cross sectional research. This research was conducted with 108 respondents from Trisakti University second-year dental students, using a questionnaire. The author distributes the questionnaire and informed consent in the form of google form, respondents were given 20 minutes to fill out the questions provided. The data is presented in frequency distribution table. Results: From 108 respondents, 90 students (83.3%) had a good level of knowledge about the differences between clear aligner and orthodontic fixed appliance, 15 other students had minimum knowledge, and 3 other students had poor knowledge. When viewed seperately, there are 72 students (66.7%) who have a good level of knowledge in clear aligners, and 84 students (77.8%) who have a good level of knowledge in orthodontic fixed appliance. Conclusion: Trisakti University second-year dental students understood the difference in the effectiveness of clear aligners and fixed appliances based on good prior knowledge of 83.3%. When compared, the understanding of the Trisakti University second-year dental students regarding fixed appliance (77.8%) tends to be better than clear aligners (66.7%).